Legal aspects of mortgage lending for military personnel - Nakonechny , Vasyl (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article is devoted to the legal aspects of mortgage lending for military personnel in Ukraine. It analyzes the main legal norms regulating this process and the specific features considered when granting mortgage loans to military personnel. Special attention is paid to legislative initiatives. The article explores in detail the problems and challenges faced by military personnel and proposes possible ways to improve legislation to facilitate access to mortgage loans.The unique feature of housing mortgages is highlighted, particularly the fact that they not only provide a way to acquire housing for living but also serve as a mechanism for obtaining ownership of the property. This is of great importance for military personnel and their families, who often face difficulties in securing adequate housing. While military personnel can access mortgage loans under general conditions, in cases of mobilization or the fulfillment of official duties, their ability to meet financial obligations may be limited.It is emphasized that, in certain situations, the special legal status of military personnel may complicate or render impossible the fulfillment of mortgage obligations, even when there are existing credit agreements. Such circumstances may arise in cases of mobilization, being stationed in combat zones, or being captured, where the physical or legal capacity to meet financial obligations is significantly restricted. These factors must be considered when improving mortgage lending regulations for military personnel.Special attention is also given to the issues of mortgage lending for military personnel who have become disabled as a result of service. Individuals who have incurred disabilities while performing their duties may face significant difficulties due to reduced income levels or even the complete inability to make mortgage payments.